Contribution of Learning Style, Learning Creativity and Exploratory Interest to Students' Simulation and Digital Communication Learning Outcomes during the Covid-19 Pandemic - Ida, Febrianti Maya; Maksum, Hasan (Universitas Pendidikan Ganesha, 2020)
Many problems occur when online learning is carried out, this problem is for most students prefer face-to-face learning. Online learning is not fun because the methods used in learning are monotonous and online learning causes students to experience stress. This study aims to reveal the contribution of learning styles, creativity, and exploratory interest to the learning outcomes of simulation and digital communication during the COVID-19 pandemic. This type of research is quantitative with correlational research methods. The population of this study was students of class X. The sampling technique was proportional random sampling, with a total sample of 80 students. The data analysis technique used is quantitative data analysis techniques. Based on the research results, it was found that the data were normal, linear, and did not occur multicollinearity. The test results at a significance level of α 0.05 (95% confidence level) obtained a rx1y value of 0.380 with an r table of 0.220 because rcount> rtable, the first hypothesis was accepted. Then the rx2y value is 0.695 with rtable 0.220, because rcount> rtable, the second hypothesis is accepted. Then the rx3y value is 0.770 with r table 0.220, because rcount> rtable, the third hypothesis is accepted. Furthermore, the value of rx1x2x3y is 0.772 with rtable 0.220, because rcount> rtable, the fourth hypothesis is accepted. And supported by the value of Fcount = 37.262 and Ftable = 2.723 to obtain Fcount> Ftable. (37,262> 2,723). So, it can be concluded that there is a contribution of learning style, creativity, and exploratory interest to the learning outcomes of simulation and digital communication during the 19 covid pandemics